2013
DOI: 10.2478/s11756-013-0252-9
|View full text |Cite
|
Sign up to set email alerts
|

Biohydrologic effects of eastern redcedar encroachment into grassland, Oklahoma, USA

Abstract: Woody encroachment affects the biohydrology of rangelands worldwide and can increase evapotranspiration by increasing plant rooting depth, increasing the duration of the growing season, or by initiating a process of hydrologic recovery in formerly overgrazed landscapes. Eastern redcedar (Juniperus virginiana) is encroaching rapidly into rangelands in the Southern Great Plains of the USA, and beyond, including Oklahoma. However, the degree to which increasing growing season duration causes higher evapotranspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In the case of the Australian experience with wildfire-affected eucalypts, Nolan et al (2014) found that leaves resprouted along the trunk and branches, resulting in lower hydraulic resistance and hence higher transpiration per unit leaf area by nearly a factor of two. Therefore, despite the widespread practice of taking vegetation index as an index of transpiration (Nagler et al 2005, Wine and Hendrickx 2013, Cadol and Wine 2017, this approach is a simplification in areas in which the vegetation index-transpiration relationship changes following wildfire.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Australian experience with wildfire-affected eucalypts, Nolan et al (2014) found that leaves resprouted along the trunk and branches, resulting in lower hydraulic resistance and hence higher transpiration per unit leaf area by nearly a factor of two. Therefore, despite the widespread practice of taking vegetation index as an index of transpiration (Nagler et al 2005, Wine and Hendrickx 2013, Cadol and Wine 2017, this approach is a simplification in areas in which the vegetation index-transpiration relationship changes following wildfire.…”
Section: Discussionmentioning
confidence: 99%
“…ET was observed to decrease by an average of 0.12 mm/day (~7% of daily ET) over three years following the removal of Ashe juniper (Juniperus ashei) compared to plots without juniper removal in an experiment conducted in northeastern Texas, USA (Dugas, Hicks, & Wright, 1998). However, the magnitude of increased ET due to WPE has not been quantified at landscape scale (Archer, 2010;Wine & Hendrickx, 2013). These site-level studies found a consistent increase of ET after WPE resultant of deep-rooted woody species replacing shallow-rooted herbaceous vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…These site-level studies found a consistent increase of ET after WPE resultant of deep-rooted woody species replacing shallow-rooted herbaceous vegetation. However, the magnitude of increased ET due to WPE has not been quantified at landscape scale (Archer, 2010;Wine & Hendrickx, 2013).…”
mentioning
confidence: 99%
“…While global climate change is currently an important background condition of woody encroachment, some studies predict that more severe future climate‐change‐induced droughts will tend to minimize future woody encroachment (Lohmann et al ., ), whereas other studies suggest that increasing atmospheric CO 2 concentrations, may afford C 3 trees and shrubs with a competitive advantage over C 4 grasses (Bond and Midgley, ). The effects of woody encroachment at a given location are highly dependent on soil properties, climate, soil compaction because of grazing, rooting depth, plant growing season, and plant–water stress response (Huxman et al ., ; Seyfried and Wilcox, ; Wine and Hendrickx, ). However, the relative sensitivity of deep drainage to these factors in a landscape undergoing woody encroachment is not well known.…”
Section: Introductionmentioning
confidence: 99%